2021
DOI: 10.26434/chemrxiv.14135138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intermolecular Interaction Analyses on SARS-CoV-2 Receptor Binding Domain and Human Angiotensin-Converting Enzyme 2 Receptor-Blocking Antibody/peptide Using Fragment Molecular Orbital Calculation

Abstract: <p>The spike glycoprotein (S-protein) mediates SARS-CoV-2 entry via intermolecular interaction with human angiotensin-converting enzyme 2 (hACE2). The receptor-binding domain (RBD) of the S-protein has been considered critical for this interaction and acts as the target of numerous neutralizing antibodies and antiviral peptides. This study used the fragment molecular orbital (FMO) method to analyze the interactions between RBD and antibodies/peptides and extracted crucial residues that can be used to epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In a previous study, it was reported that the N501Y mutation enhances the ability of S protein to bind to ACE2 by acquiring more hydrogen bonds and XH/ interactions than WT 49 . As an example of RBD-neutralizing antibodies, we show the FMO results for a structure containing BD-629 Fab, which has many overlapping active sites on RBD with the ACE2 receptor and a high activity value (IC50) (PDB ID: 7CH5, FMODB ID: JM5M9) 50 . First, the main components of PIEDA for the PPI of RBD and BD-629 Fab were mapped on the molecular structure (Figures 16a,b).…”
Section: Spike (S) Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, it was reported that the N501Y mutation enhances the ability of S protein to bind to ACE2 by acquiring more hydrogen bonds and XH/ interactions than WT 49 . As an example of RBD-neutralizing antibodies, we show the FMO results for a structure containing BD-629 Fab, which has many overlapping active sites on RBD with the ACE2 receptor and a high activity value (IC50) (PDB ID: 7CH5, FMODB ID: JM5M9) 50 . First, the main components of PIEDA for the PPI of RBD and BD-629 Fab were mapped on the molecular structure (Figures 16a,b).…”
Section: Spike (S) Proteinmentioning
confidence: 99%
“…These results suggest that Lys417 and Asn501, which are characteristic of South African and Brazilian mutants, contribute significantly to the interaction with neutralizing antibodies similar to the ACE2 receptor. Details of the epitope analysis by neutralizing antibodies50 and mutant strains 51 are available in the respective references.…”
mentioning
confidence: 99%